KARAKTERISTIK DAN KUALITAS ABSTRAK JURNA ILMU PERPUSTAKAAN, DOKUMENTASI DAN INFORMASI DI INDONESIA TAHUN 2015 - Rochani Nani Rahayu (Perpustakaan Nasional RI, 2019)
This is a study of journal abstract quality in the field of library, documentation and information (Perpusdokinfo) in 2016 of 10 journals in Indonesia that have used open journal system. The study used assesment method with references criteria SNI 19-4192-2002. The aims of the study wear to find out: a) The quality of Perpusdokinfo journal abstracts published by Univercities; b) The quality of Perpusdokinfo journal abstract published by Islamic Universities: c) The quality of Perpusdokinfo journal abstracts published by non-tertiary institutions: d) The quality of Perpusdokinfo journal abstracts published in Java and outside Java. The methodology carried out was an assesment of ten abstracts from Perpusdokinfo journal. The analysis carried out in a simple way the refered to SNI 19-4192-2002. The study result that the quality of abstract published by universities was in the first position; it was the information studies journal of unpad library with the score percentage of 94,74%, good grade. Then, with average falue of 39, 95%, there is not good quality abstracts published by Islamic universities found. The quality of Perpusdokinfo journal abstarcts published by non tertiary instituions has good grade with the percentage of 100%. The quality of journal absctract publihesd in java was of good grade with the precentage of 71,27 % and 51,28% for those published outside Java. The conclutions was that the quality of journal abstract published by non-tertiary institutions ranks first with the precentage of the good grade was 100%; in the second place was choose published by universities; and choose published by Islamic Universities was in the 3rd position. The quality of pPerpusdokinfo journal published in the java wa higher than those published outside java.